The Passive Mixing Phenomena in Microtubes with Baffle Configuration. (2016) - Milotin, Roxana; Lelea, Dorin
Abstract: The paper presents the analysis on passive mixing phenomena in microtubes considering three different configurations. Two of them having four baffles that create orifice with half and respectively quarter of the cross-section that are compared with the simple microtube. The micromixers have four inlet cross-sections with water and methanol as the working fluids. The mixing efficiency is evaluated through the mixing index that considers the standard deviation of the mass fraction at specific cross-section. Moreover the analysis is extended to Re = 0.2 – 91 in order to analyze the axial mixing length for each case considered. The analysis is performed numerically based on a finite volume code. It was concluded that best mixing results have the microtubes with orifices that occupy the quarter of the cross-section both for low Re and diffusion mixing or higher Re and mixing augmented by advection.